The SL(2,C)-character varieties of torus knots - Muñoz, Vicente (Revista Matemática Complutense, 2009)
Let G b e the fundamental group of the complement of the torus knot of typ e (m, n). This has a presentation G = x, y | xm = y n . We find the geometric description of the character variety X (G) of characters of representations of G into SL(2, C).